Shake Table Tests on Single-Story Dhajji Dewari Traditional Buildings. Issue 7 (3rd October 2017) - Ali, Qaisar; Ahmad, Naveed; Ashraf, Muhammad; Rashid, Muhammad; Schacher, Tom
ABSTRACT: This article presents shake table tests carried out on two reduced scaled models, including 1/3 rd scaled single room model and 1/4 th scaled two rooms house model Dhajji Dewari (timber-braced frame rubble stone masonry) traditional structures for seismic performance evaluation. Multiple excitations tests were performed on the model structures using natural accelerograms with increasing intensity to deform the structure from elastic to inelastic and extreme damage state. The structure observed damage states, acceleration, and displacement response and lateral force-deformation behavior are retrieved. The tested structure models showed an excellent performance under the earthquake ground motions; deforming to large lateral displacement without jeopardizing the global stability despite extreme level shaking and observed localized damages. The model under bi-directional loading, reproduced through diagonal excitation, was observed with relatively reduced lateral strength and lateral deformation, due to walls subjected to both in-plane and out-of-plane loading. The research highlights the importance of dynamic excitation on the seismic performance evaluation of Dhajji structures. Analytical models are used for the capacity evaluation of considered Dhajji buildings, which shows promising performance in calculating the building yield stiffness and strength. Displacement-based method is used for the intensity-based seismic performance assessment of individual building in the highest seismic zone (PGA = 0.40 g, Soil Type D), which shows that Dhajji building under orthogonal loading will not exceed even the Immediate Occupancy level under design level earthquake ground motions. However, the building can just exceed the Life Safety level in design level ground motions, under diagonal excitation.